New giant planet beyond the snow line for an extended MOA exoplanet microlens sample. Issue 1 (26th June 2021) - Ranc, Clément; Bennett, David P; Barry, Richard K; Koshimoto, Naoki; Skowron, Jan; Hirao, Yuki; Bond, Ian A; Sumi, Takahiro; Bathe-Peters, Lars; Abe, Fumio; Bhattacharya, Aparna; Donachie, Martin; et al.
ABSTRACT: Characterizing a planet detected by microlensing is hard if the planetary signal is weak or the lens-source relative trajectory is far from caustics. However, statistical analyses of planet demography must include those planets to accurately determine occurrence rates. As part of a systematic modelling effort in the context of a >10-yr retrospective analysis of MOA's survey observations to build an extended MOA statistical sample, we analyse the light curve of the planetary microlensing event MOA-2014-BLG-472. This event provides weak constraints on the physical parameters of the lens, as a result of a planetary anomaly occurring at low magnification in the light curve. We use a Bayesian analysis to estimate the properties of the planet, based on a refined Galactic model and the assumption that all Milky Way's stars have an equal planet-hosting probability. We find that a lens consisting of a 1.9^+2.2_-1.2 M_J giant planet orbiting a 0.31^+0.36_-0.19 M_ host at a projected separation of 0.75± 0.24 au is consistent with the observations and is most likely, based on the Galactic priors. The lens most probably lies in the Galactic bulge, at 7.2^+0.6_-1.7 kpc from Earth. The accurate measurement of the measured planet-to-host star mass ratio will be included in the next statistical analysis of cold planet demography detected by microlensing.